2012
DOI: 10.1523/jneurosci.3017-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Kainate Receptor-Induced Retrograde Inhibition of Glutamatergic Transmission in Vasopressin Neurons

Abstract: Presynaptic kainate receptors (KARs) exert a modulatory action on transmitter release. We here report that applications of agonists of GluK1-containing KARs in the rat supraoptic nucleus has an opposite action on glutamatergic transmission according to the phenotype of the postsynaptic neuron. Whereas glutamate release was facilitated in oxytocin (OT) neurons, it was inhibited in vasopressin (VP) cells. Interestingly, an antagonist of GluK1-containing KARs caused an inhibition of glutamate release in both OT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…A previous study showed that presynaptic glutamate release was facilitated in OXT neurones by ATPA but was inhibited in AVP neurones . By contrast, AVP neurones (but not OXT neurones) express functional postsynaptic GluK1‐containing KARs . Unexpectedly, our results demonstrated that GluK1‐containing KARs are expressed in both AVP‐eGFP and OXT‐mRFP1 neurones.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…A previous study showed that presynaptic glutamate release was facilitated in OXT neurones by ATPA but was inhibited in AVP neurones . By contrast, AVP neurones (but not OXT neurones) express functional postsynaptic GluK1‐containing KARs . Unexpectedly, our results demonstrated that GluK1‐containing KARs are expressed in both AVP‐eGFP and OXT‐mRFP1 neurones.…”
Section: Discussionsupporting
confidence: 48%
“…A previous study showed that presynaptic glutamate release was facilitated in OXT neurones by ATPA but was inhibited in AVP neurones . By contrast, AVP neurones (but not OXT neurones) express functional postsynaptic GluK1‐containing KARs .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…After recording, magnocellular neurones filled with biocytin (0.1%) were identified further by immunocytochemistry as previously described (Bonfardin et al 2012). At the end of the recording period, slices were fixed by immersion in 4% paraformaldehyde and 0.15% picric acid (2 h, room temperature and during 2 or 3 days at 4°C).…”
Section: Cell Identificationmentioning
confidence: 99%